If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.50x + 4(x + -1) = 23 Reorder the terms: 0.50x + 4(-1 + x) = 23 0.50x + (-1 * 4 + x * 4) = 23 0.50x + (-4 + 4x) = 23 Reorder the terms: -4 + 0.50x + 4x = 23 Combine like terms: 0.50x + 4x = 4.5x -4 + 4.5x = 23 Solving -4 + 4.5x = 23 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 4.5x = 23 + 4 Combine like terms: -4 + 4 = 0 0 + 4.5x = 23 + 4 4.5x = 23 + 4 Combine like terms: 23 + 4 = 27 4.5x = 27 Divide each side by '4.5'. x = 6 Simplifying x = 6
| 2+(7)=3 | | 6x^2-19x+8= | | X+(-70)=24 | | 6n=68 | | -6n=68 | | 2x-6=y+8 | | v^3-4v^2=0 | | 3n=-156 | | 6n-6=68 | | (6x-5)(6x+5)=12 | | Z+(-3)=4 | | 3(10-2x)-12=-2(x-11)+4 | | 0/0=0 | | 10z-10=4z+20 | | 3(x-4)+9=-2 | | x/4-812 | | x^5-2x^4-8x^3+20x^2+15x-50=0 | | 2/fs=18 | | 6r=32 | | 4(b-2)10=2(b+3) | | -8w+4(w-4)=12 | | -3(x+9)+7x=49 | | 3z-2=z+12 | | X/80=3/20 | | Y=-16t(2)+96t+3 | | -2z-1=z+2 | | (4u+5)(8+u)=0 | | 9X-15-2X=-60+9 | | 9=d/-3 | | -2z-1=-z+2 | | 2(4x+3x)+6=32 | | f(3)=252-15x |